Peran Guru dalam Penanganan Perilaku Anak Hiperaktif di TK Syamil Kids - Eny Arita; Havid Surya; Lira Erwinda (Jurnal Syntax Admiration, 2024)
Hyperactive behavior in children often affects the social-emotional quality of the surrounding environment. For this reason, the importance of conducting research on the role of teachers in handling hyperactive behavior in children at Syamil Kids Kindergarten becomes even more urgent considering that teachers are the figures who interact most with children during the learning process. This research aims to explore the role and challenges faced by teachers in handling the behavior of hyperactive children. This research uses a qualitative approach method. Data collection techniques were carried out by means of interviews with school principals, teachers, parents and direct observation of children. Meanwhile, data analysis in this research was carried out using interview transcripts, observation, coding and thematics. The results of this research show that the role of teachers in handling hyperactive behavior in early childhood is carried out by paying attention to: 1) classroom management strategies 2) taking an individual approach 3) teachers play a role in helping hyperactive children interact with their friends. Meanwhile, the challenges faced by teachers in handling hyperactive children are: 1) classroom management has not been able to facilitate hyperactive children to focus on the tasks given to them 2) there is no accompanying teacher to accompany hyperactive children 3) there is no teacher training on how to handle hyperactive children's behavior in kindergarten. Syamil Kids 4) difficulty in accepting parents regarding weaknesses in children with hyperactive behavior.